Proceso de atención de enfermería en paciente pediátrico con neumonía no especificada más convulsión febril. - Medina Veliz, Willy Santiago (2021)
Through the study and development of my clinical case, I say that the application of the nursing care process was essential. Because it is an important and indispensable work method that consists of a system with related steps that will allow us to identify and satisfy all the needs required by the patient. And so too, solve the health problems that affect the human being in their context, family and the community. Reason why, this present research work was carried out with the main objective of applying the nursing care process in a 4-month-old pediatric patient who was diagnosed with unspecified pneumonia plus febrile seizure, due to presenting a picture clinical presentation of tachypnea, tachycardia, hyperthermia, intercostal drawing and tonic-clonic seizures on 2 occasions. However, at the time of admission, the assessment was carried out using two techniques. The first was data collection where subjective data provided by a relative of the patient were interviewed and obtained, and secondly, the assessment was carried out by means of a physical examination of the patient. However, all the data collected served to be able to formulate the nursing diagnoses after having detected the dysfunctional patterns to be treated, in order to carry out the planning and execution of the nursing activities, according to those necessary that the patient requires to contribute in restoring your health during your hospitalization.